2018
DOI: 10.1007/s13337-018-0418-8
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of RNA silencing encoded by geminiviruses and associated DNA satellites

Abstract: In plants, RNA silencing provides a major line of defence against viruses. This antiviral immunity involves production of virus-derived small interfering RNAs (vsiRNAs) and results in specific silencing of viruses by vsiRNAs-guided effector complexes. As a counterattack against RNA silencing, many plant viruses encode suppressors of RNA silencing called viral suppressors of RNA silencing (VSRs), which interfere with the silencing pathway by various mechanisms. This review describes various methods that are bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…To our knowledge, independent studies have identified that V2, C1, C2, C4/AC4 and βC1 encoded by different geminiviruses can suppress PTGS and/or TGS [ 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Besides, previous reports have shown that V2 proteins encoded by begomoviruses with or without betasatellite have diverse functions for infection.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, independent studies have identified that V2, C1, C2, C4/AC4 and βC1 encoded by different geminiviruses can suppress PTGS and/or TGS [ 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Besides, previous reports have shown that V2 proteins encoded by begomoviruses with or without betasatellite have diverse functions for infection.…”
Section: Introductionmentioning
confidence: 99%
“…The arms race between silencing and silencing suppression results in resistance or susceptibility to the pathogen. Geminiviruses encode several proteins namely AC2/C2, AC4/C4, AV2/V2, βC1, and Rep that suppress RNA silencing by targeting various components of the post-transcriptional gene silencing (PTGS) machinery, transcriptional gene silencing (TGS) machinery, and cellular regulatory genes (reviewed in Hanley-Bowdoin et al, 2013;Kumar, 2019;Rishishwar and Dasgupta, 2019;Yang et al, 2019;Guerrero et al, 2020). Of all the known geminiviral suppressor proteins, AC2 is the most well-studied and is known to target multiple plant genes and proteins.…”
Section: Plant Defense and Viral Counter-defense Mechanismsmentioning
confidence: 99%
“…RNA silencing is considered as a major line of defense against pathogens such as viruses. Plants also have the capability to produce siRNA in response to dsRNA (Rishishwar and Dasgupta, 2019). However, most of the viruses encode proteins against this plant defense response.…”
Section: Relationship Of Clcuv With Whiteflymentioning
confidence: 99%
“…SiRNAs are formed when endonuclease dicer enzymes act on long dsRNA and cleave them which later bind with their complementary sequence for transcriptional or post transcriptional gene silencing. Contrarily, microRNAs are transcribed by their own genes or from fold back structures with double stranded regions from introns (Rishishwar and Dasgupta, 2019). In plants, these primary microRNAs are processed in the nucleus by the dicer enzymes into pre or precursor miRNA which later form duplexes before being exported to the RISCs (Sattar et al, 2013).…”
Section: Relationship Of Clcuv With Whiteflymentioning
confidence: 99%